Molecular Screening of Blood Donors for Babesia in Tyrol, Austria - Bloch, Evan M.; Siller, Anita; Tonnetti, Laura; Drews, Steven J.; Spencer, Bryan R.; Hedges, Doris; Mergenthal, Tessa; Weber-Schehl, Marijke; Astl, Manfred; Patel, Eshan U.; Gaber, Manfred; Schennach, Harald (Transfusion medicine and hemotherapy, 2023)
Introduction: Babesia is a tick-borne intraerythrocytic parasite that is globally ubiquitous, yet understudied. Several species of Babesia have been shown to be transfusion-transmissible. Babesia has been reported in blood donors, animals, and ticks in the Tyrol (Western Austria), and regional cases of human babesiosis have been described. We sought to characterize the risk of Babesia to the local blood supply. Methods: Prospective molecular testing was performed on blood donors who presented to regional, mobile blood collection drives in the Tyrol, Austria (27 May to October 4, 2021). Testing was conducted using the cobas ® Babesia assay (Roche Molecular Systems, Inc.), a commercial PCR assay approved for blood donor screening that is capable of detecting the 4 primary species causing human babesiosis (i.e., B. microti, B. divergens, B. duncani, and B. venatorum). A confirmatory algorithm to manage initial PCR-reactive samples was developed, as were procedures for donor and product management. Results: A total of 7,972 donors were enrolled and screened; 4,311 (54.1%) were male, with a median age of 47 years (IQR = 34–55). No positive cases of Babesia were detected, corresponding with an overall prevalence of 0.00% (95% CI: 0.00%, 0.05%). Discussion: The findings suggest that the prevalence of Babesia is low in Austrian blood donors residing in the Tyrol, even during months of peak tick exposure. Although one cannot conclude the absence of Babesia in this population given the limited sample size, the findings suggest that the regional risk of transfusion-transmitted babesiosis is low.